Effect of nutrient and density against the susceptibility status of Aedes aegypti and aedes albopictus towards diagnostic dose of malathion and permethrin - Salinah Abdul Farouk,; Zairi Jaal,; Siti Nasuha Hamzah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The knockdown 50% values (KT50) of Aedes aegypti and Aedes albopictus with variable nutrient and density conditions were determined based on World Health Organisation (WHO) Adult Bioassay standard protocol towards diagnostic dose of malathion (5%) and permethrin (0.75%) and the effect of nutrient and density on Aedes susceptibility status were investigated. Our results revealed that the susceptibility of these Aedes mosquitoes against malathion at F (4, 116) = 42.103, p<0.05 and permethrin at F (4, 121) = 45.138, p<0.05, gives the most delayed knockdown when fed with the optimum amount of nutrient which is 70mg compared with the lower amount of nutrient and the survival decreased once the nutrient amount was increased more than this amount. For density effect against Aedes susceptible status, at the highest density (600 larvae) examined, there was proportionally more larval mortality where the KT50 value was at the lowest value when compared with the optimal density which was between 150 to 250 larvae against malathion at F (6, 159) = 62.203, p<0.05 and permethrin at F (6, 148) = 57.431, p<0.05. However, the effect of nutrient and density factor of the different Aedes species significantly impacted their susceptibility to malathion and permethrin. The time required to knock down 50% (KT₅₀) of Ae. albopictus mosquitoes against the diagnostic dose of malathion as well as permethrin were relatively delayed compared to the values obtained by Ae. aegypti mosquitoes even though the environmental conditions were the same (p<0.05).